2010
DOI: 10.1016/j.jneuroim.2009.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment following high fat diet consumption is associated with brain inflammation

Abstract: C57Bl/6 mice were administered a high fat, Western diet (WD, 41% fat) or a very high fat lard diet (HFL, 60% fat), and evaluated for cognitive ability using the Stone T-maze and for biochemical markers of brain inflammation. WD consumption resulted in significantly increased body weight and astrocyte reactivity, but not impaired cognition, microglial reactivity, or heightened cytokine levels. HFL increased body weight, and impaired cognition, increased brain inflammation, and decreased BDNF. Collectively, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
368
9
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 512 publications
(407 citation statements)
references
References 85 publications
18
368
9
1
Order By: Relevance
“…Studies from our laboratory and others' have demonstrated that HFDs exacerbate tissue dysfunction in aging animals (11,29,46,68,76). Additionally, studies from our laboratory and others' have shown that HFDs promote much greater amounts of adipose gain, and presumably adipose tissue dysfunction, compared with younger animals (46,50,66). These data point to important, and as yet unknown, interactions between obesity and aging.…”
Section: Discussionmentioning
confidence: 53%
“…Studies from our laboratory and others' have demonstrated that HFDs exacerbate tissue dysfunction in aging animals (11,29,46,68,76). Additionally, studies from our laboratory and others' have shown that HFDs promote much greater amounts of adipose gain, and presumably adipose tissue dysfunction, compared with younger animals (46,50,66). These data point to important, and as yet unknown, interactions between obesity and aging.…”
Section: Discussionmentioning
confidence: 53%
“…52). Some of these peripheral effects, such as oxidative stress, also occur in the brain following HF feeding (21,40,58), and HF feeding increases cognitive impairment, tau deposition, MPTP vulnerability, and inflammation in the brain (15,38,44,45). Although specific contributions of other HF diet effects cannot be ruled out, our observation of increased markers of insulin resistance in the absence of increased total cholesterol or LDL-C levels and a positive correlation between HOMA-IR and DA depletion support a role for insulin resistance in mediating increased toxin-induced DA depletion.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is now considered an 'inflammatory condition' that is associated with elevated peripheral and vascular pro-inflammatory profiles (Scarpellini and Tack 2012;Sun et al 2012) and central inflammatory changes including gliosis and activation of the cerebrovasculature in the brains of obese and high-fat fed rodents (Pistell et al 2010;Drake et al 2011;Thaler et al 2012). It is generally considered that peripheral inflammation is a consequence of obesity, however, recent data suggests that central inflammation actually precedes weight gain in high-fat fed rodents (Thaler et al 2012).…”
Section: Obesity/metabolic Syndromementioning
confidence: 99%